Comparison of growth, carcass and meat quality characteristics of triploid and diploid Black Sea trout (Salmo trutta labrax) under laboratory conditions - Delihasan Sonay, F; Başçınar, N; Akhan, S (Journal of the Hellenic Veterinary Medical Society, 2024)
This study compared the growth performance of triploid and diploid Black Sea trout (Salmo trutta labrax) during their fry (initial weight 0.21 – 0.21 g), fingerling (1.97 – 2.08 g) and juvenile (52.15 – 57.81 g) stages. The carcass ratio, gonadosomatic index (GSI), hepatosomatic index (HIS), proximate and fatty acid composition for the juvenile fish were also investigated. The results evinced no metabolic advantage resulting from triploidy before sexual maturation of Black Sea trout as the triploid growth was equal to diploid siblings. The juvenile triploid Black Sea trout grew faster than diploid having significantly higher weight gain, length increment, thermal growth coefficient, specific growth rate, and lower feed conversion ratio. The GSI values tended to increase over time in diploid and their significantly lower values were observed in triploid in the last three months of the trial. The HSI of triploids were significantly higher than diploid siblings. Triploid had significantly higher fat contents, and possessed higher levels of saturated and monounsaturated fatty acids than diploid. Diploid had higher polyunsaturated fatty acids than triploid siblings. These findings indicate the potential for superior triploid growth with better carcass ratio suggesting a great benefit of induced triploidy in Black Sea trout culture.